Monitoring the Change of Protein Expression in Human Colon Cancer Cell SNU-81 treated with the Water-Extract of Coptis japonica - Byung-Soo Kim; Tae-Mo Yoo; Byong-Chul Yoo; Hwa-Seung Yoo (Journal of Pharmacopuncture, 2009)
Background : Anticancer effects of herbal medicine have been reported in various types of cancer, but the systematic approaches to explain molecular mechanism(s) are not established yet. Objective : To find the anticancer-effect and mechanism(s) of Water Extract of Coptis japonica (WECJ) colon cancer cell (SNU-81). Methods : We first selected 11 herbals, and anti-cancer effects of water-extracts from those herbals have been tested in human colon cancer cell line, SNU-81. Among the tested herbals, the WECJ significantly reduced proliferation of SNU-81. To establish a basis of understanding for anti-cancer mechanism, whole proteins have been obtained from SNU-81 harvested at 48 and 96 hrs after the treatment of WECJ, protein expression has been profiled by 2DE-based proteomic approach. Results : Various changes of the protein expression have been monitored, and most frequent dysregulation was found in the molecular chaperons including heat shock protein 90-alpha (Hsp90-alpha), 14-3-3 protein epsilon, T-complex protein 1 subunit alpha, protein disulfide-isomerase A3, and calreticulin. Interestingly, proliferation-associated protein 2G4 has been up-regulated, and it suggests the possible effect of Coptis japonica on ErbB3-regulated signal transduction pathway and growth control of human colon cancer cells. Conclusion : Based upon the present findings, the further study will focus on monitoring various cancer survival factors after artificial regulation of the proteins identified, and it would be the basis for the understanding of the Coptis japonica anti-cancer effect(s) at the molecular level.